2020
DOI: 10.1021/acs.est.9b07928
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Partial-Denitrification, Anammox, and in-situ Fermentation (SPDAF) Process for Advanced Nitrogen Removal from Domestic and Nitrate-Containing Wastewater

Abstract: This study presents a new method for energy-efficient wastewater treatment that synergizes the partial-denitrification, anammox, and in-situ fermentation (SPDAF) processes in an up-flow reactor. Nitrate-containing wastewater and actual domestic sewage were fed into this SPDAF system, which was operated for 180 days without the addition of external carbon sources and aeration. The total inorganic nitrogen (TIN) removal efficiency reached 93.1% with a low C/N ratio of 1.6, a NO3 ––N/NH4 +–N ratio of 1.13 and a T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…C/N is the key to start an anammox and partial denitrication coupling reactor, and it is also an important control parameter to maintain stable reactor operation and efficient nitrogen removal. 19,30,125 The presence of organic matter is generally believed to have adverse effects on the anammox process because the heterotrophic denitrifying bacteria grow at a much higher rate and with a higher cellular synthesis growth yield compared to autotrophic anammox bacteria. 106 Anammox bacteria are autotrophic bacteria, and the participation of organic carbon will inhibit bacterial growth.…”
Section: Conclusion and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…C/N is the key to start an anammox and partial denitrication coupling reactor, and it is also an important control parameter to maintain stable reactor operation and efficient nitrogen removal. 19,30,125 The presence of organic matter is generally believed to have adverse effects on the anammox process because the heterotrophic denitrifying bacteria grow at a much higher rate and with a higher cellular synthesis growth yield compared to autotrophic anammox bacteria. 106 Anammox bacteria are autotrophic bacteria, and the participation of organic carbon will inhibit bacterial growth.…”
Section: Conclusion and Evaluationmentioning
confidence: 99%
“…It is worth noting that in the long-term and short-term effects of pH on denitrication, a high pH value is benecial to achieve partial denitrication of nitrite accumulation. [147][148][149] The SPDAF (synergizes the partial denitrication, anammox and in situ fermentation) collaborative process established by Ji et al 30 has the disadvantages of slow degradation of organic matter and low utilization rate. The sludge in the fermentation tank was inoculated into the UASB reactor to promote denitrication.…”
Section: Reactor Quick Start Strategymentioning
confidence: 99%
“…As we all known, the key reason for efficient nitrogen removal via PDA process was the coexistence of diverse microbial flora, owing to PD biomass known as classical heterotrophic bacteria along with intense proliferation growth might lead to autotrophic anammox bacteria possibly inhibited. Notably, maintaining dominant anammox nitrogen removal pathway was essential, since researchers have reported that anammox contributed more than 95% nitrogen removal in PDA [11]. On the other hand, PD occurred ahead of anammox was a prerequisite due to NO 2 --N-electron acceptor supply must be warranted for anammox microbes [1].…”
Section: Characteristics Of Pda Coupling Processmentioning
confidence: 99%
“…Du et al conducted two sludge nitrification and PDA reactor to treat real municipal sewage and artificial nitrate wastewater with sodium acetate solution as external organics, achieving as low as 5 mg/L TN effluent despite frequent temperature fluctuations (16.3~25.7°C) [10]. In addition, Ji et al successfully coupled in-situ fermentation with PDA in a single reactor for advanced nitrogen removal from domestic and nitrate-containing wastewater, and the slowly biodegradable organics could be hydrolyzed and acidized to volatile fatty acids (VFAs) via fermentation, thus in-situ carbon source generated for further NO 3 --N reduction without external addition [11]. This provided new insight into practical application of PDA in a cost-effective and environmental-friendly way.…”
Section: Carbon Sourcesmentioning
confidence: 99%
See 1 more Smart Citation